تحديد تراكيز النحاس والتوتياء في بعض أنواع البهارات في السوق المحلية - سليمان, فؤاد; عليا, تميم أحمد (Latakia University Journal -Biological Sciences Series, 2013)
قدرت كمية عنصرين من العناصر الثقيلة (النحاس والتوتياء) في بعض أنواع البهارات شائعة الاستعمال والمنتشرة في بعض الأسواق المحلية السورية باستخدم جهاز الامتصاص الذري. بينت الدراسة وجود فروق في تراكيز هذين العنصرين تبعاً لأنواع البهارات المختلفة المدروسة. تراوح تركيز النحاس في البهارات من تراكيز صغيرة (0.059) إلى تراكيز عالية وصلت إلى 0.668 mg/kg. بينما وصل الحد الأعظمي لتركيز التوتياء في عيّنات البهارات المدروسة إلى 2.523mg/kg. كانت تراكيز النحاس في معظم العيّنات أقل من الحد الأعظمي المسموح به كما أظهرت النتائج وجود التوتياء بنسب أقل بكثير من النسب المسموح بها في المواصفات العالمية والمحلية. The concentrations of Copper (Cu) and Zinc (Zn) in samples of some spices available at some local markets in Syria were determined, after nitric digestion, using Atomic Absorption Spectrometry. The study showed differences in metal concentrations according to the edible part. Studied heavy metals were present in all samples at different levels. The concentration of Copper (Cu) and Zinc varied from trace to higher concentration. The maximum level of Copper (Cu) in the spices samples was 0.668 mg/kg. The maximum level of Zinc (Zn) in the spices samples was 2.523mg/kg. The analytical results obtained for the heavy metals indicate that the Copper and Zinc were present in all samples at concentration well below the acceptable daily intake recommended by the World Health Organization.